MOTIVASI PENYULUH PERTANIAN DALAM MELAKSANAKAN KEGIATAN PENYULUHAN DI LINGKUP KERJA BPP KECAMATAN BENUA KABUPATEN KONAWE SELATAN - Abdullah, Sukmawati (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
This study aims to identify and analyze the motivation of agricultural extension workers in carrying out extension activities within the scope of work of the BPP Benua District, South Konawe Regency. Agricultural extension plays an important role in increasing the capacity of farmers through effective extension. The motivation of the extension workers can influence the success in conveying information and motivating farmers to implement better agricultural technology. The sampling technique was carried out by census sampling, namely to all agricultural extension workers in the BPP Benua District, totaling 7 people. Data analysis used is qualitative descriptive analysis by classifying the level of motivation of agricultural extension workers into three groups: low, medium and high. The results of the study indicate that: intrinsic factors of agricultural extension workers (physiological needs, needs for self-realization, social needs, needs for security and needs to be given) provide motivation for agricultural extension workers in carrying out their activities in the high category. While extrinsic motivation (operational vehicles, honor/salary, operational costs and extension aids) provide motivation that is classified as medium. This research can provide recommendations for local government policies in increasing the motivation of extension workers so that they can be more optimal in implementing it, which will ultimately have an impact on improving the welfare of farmers in South Konawe Regency.